Developing technical support and strategic dialogue at the country level to achieve Primary Health Care-based health systems beyond the COVID-19 era - Cheong Chi Mo, Jeremy; Shah, Archana; Downey, Casey; Genay-Diliautas, Sophie; Saikat, Sohel; Mustafa, Saqif; Meru, Nikon; Dalil, Suraya; Schmets, Gerard; Porignon, Denis (Frontiers in Public Health, 2023)
This article is part of the Research Topic ‘Health Systems Recovery in the Context of COVID-19 and Protracted Conflict’. Pursuing the objectives of the Declaration of Alma-Ata for Primary Health Care (PHC), the World Health Organization (WHO) and global health partners are supporting national authorities to improve governance to build resilient and integrated health systems, including recovery from public health stressors, through the long-term deployment of WHO country senior health policy advisers under the Universal Health Coverage Partnership (UHC Partnership). For over a decade, the UHC Partnership has progressively reinforced, via a flexible and bottom-up approach, the WHO’s strategic and technical leadership on Universal Health Coverage, with more than 130 health policy advisers deployed in WHO Country and Regional Offices. This workforce has been described as a crucial asset by WHO Regional and Country Offices in the integration of health systems to enhance their resilience, enabling the WHO offices to strengthen their support of PHC and Universal Health Coverage to Ministries of Health and other national authorities as well as global health partners. Health policy advisers aim to build the technical capacities of national authorities, in order to lead health policy cycles and generate political commitment, evidence, and dialogue for policy-making processes, while creating synergies and harmonization between stakeholders. The policy dialogue at the country level has been instrumental in ensuring a whole-of-society and whole-of-government approach, beyond the health sector, through community engagement and multisectoral actions. Relying on the lessons learned during the 2014–2016 Ebola outbreak in West Africa and in fragile, conflict-affected, and vulnerable settings, health policy advisers played a key role during the COVID-19 pandemic to support countries in health systems response and early recovery. They brought together technical resources to contribute to the COVID-19 response and to ensure the continuity of essential health services, through a PHC approach in health emergencies. This policy and practice review, including from the following country experiences: Colombia, Islamic Republic of Iran, Lao PDR, South Sudan, Timor-Leste, and Ukraine, provides operational and inner perspectives on strategic and technical leadership provided by WHO to assist Member States in strengthening PHC and essential public health functions for resilient health systems. It aims to demonstrate and advise lessons and good practices for other countries in strengthening their health systems.